2020
DOI: 10.3855/jidc.13274
|View full text |Cite
|
Sign up to set email alerts
|

Nitazoxanide against COVID-19 in three explorative scenarios

Abstract: Introduction: Nitazoxanide has shown efficacy in vitro against coronavirus infections (MERS, SARS, SARS-CoV-2). The aim of this report is to describe the results of treating COVID-19 positive patients with nitazoxanide in three clinical settings: pregnancy/puerperium, hospitalized patients in an Internal Medicine Service and in an ambulatory setting. Methodology: This was a prospective follow-up and report of COVID-19 cases in three different situations, pregnant women, hospitalized patients receiving me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0
6

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 21 publications
0
25
0
6
Order By: Relevance
“…Efficacy of azithromycin is well established in cases of community acquired pneumonia (CAP), but it is effects on viruses lacks evidence (Sultana et al 2020 ). Besides azithromycin, clarithromycin has also been used in COVID-19 patients (Calderón et al 2020 ). WHO has also reported the widespread use of azithromycin especially with hydroxychloroquine even beyond recommendations (WHO 2020 , NICE 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Efficacy of azithromycin is well established in cases of community acquired pneumonia (CAP), but it is effects on viruses lacks evidence (Sultana et al 2020 ). Besides azithromycin, clarithromycin has also been used in COVID-19 patients (Calderón et al 2020 ). WHO has also reported the widespread use of azithromycin especially with hydroxychloroquine even beyond recommendations (WHO 2020 , NICE 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…46,47 Nitazoxanide is safe to take during pregnancy (Category B), but proper dosing remains uncertain for purposes of PrEP. 48 Tafenoquine is contraindicated in pregnancy due to inadequate human data (no assigned pregnancy category) and potential risk of abortion based on animal studies. 49 A recent British study found that macrolides taken during pregnancy may be associated with an increased risk of birth defects.…”
Section: Other Options For Pregnancy Prepmentioning
confidence: 99%
“…Nitazoxanide, previously used as an antihelminthic agent, has proved an in vitro broad antiviral activity and is known to have a relatively favourable safety profile [11]. A study published by Calderon M et al on 17 pregnant women reported positive results [52]. Camostat mesylate, used in Japan for the treatment of pancreatitis, also proved an antiviral activity in vitro by preventing the virus entry into the cells, through inhibition of a host serine protease [11].…”
Section: Other Drugsmentioning
confidence: 99%